AB0087 Macrophage Migration Inhibitory Factor, Resistin, Leptin, Adiponectin and Clinical Variables in Systemic Lupus Erythematosus. (10th June 2014) - Diaz Rizo, V.; Fajardo-Robledo, N.; Trujillo, X.; Muñoz-Valle, J.; Gonzalez-Lopez, L.; Gamez-Nava, J.
Abstract : Background: Macrophage migration inhibitory factor (MIF) is a cytokine with proinflammatory properties with potential interest in systemic lupus erythematosus (SLE)1 . Also adipokines have interest in this disease. Nevertheless, the relationship between MIF and adipokines such as resistin, leptin and adiponectin with the clinical characteristics of the patients has not been consistently evaluated. Objectives: To evaluate the association between MIF and adipokines levels with disease characteristics in systemic lupus erythematosus. Methods: One-hundred and two women with SLE and 43 controls were included in a cross-sectional study. Serum levels of MIF, resistin, leptin and adiponectin were measured by ELISA. Other assessments included modified-SLEDAI (m-SLEDAI) for disease activity, SLICC/ACR, clinical variables and Body Mass Index (BMI). Statistical analysis included Student t-test for independent samples in order to compare means between groups, Pearson correlations were used to identify whether MIF and the adipokines levels were associated disease characteristics. Results: In SLE group the mean age was 43.09±11.39 years, all patients received corticosteroids. Twenty-nine patients with SLE, had proteinuria (≥0.05g/vol). MIF serum levels were higher in patients with disease activity (m-SLEDAI ≥3) compare with patients with m-SLEDAI ≥3 (13.46±9.49 vs 10.06±6.33 respectively, p=0.05). Resistin levels in SLE patients were significantly correlated with, serum levels of urea (r=0.746, p=0.001), uric acid (r=0.366, p=0.001), creatinine (r=0.342, p=0.001), prednisone doses (mg/day) (r=0.434, p=0.001) and leptin levels (r=0.228, p=0.021), but these levels did not correlated with adiponectin. Leptin levels correlated with, body mass index (BMI) (r=0.343, p<0.001), waist/hip circumference (r=0.341, p=0.002) and prednisone doses (r=0.334, p=0.001). A negative correlation was observed between adiponectin levels with BMI (r=-0.215, p=0.031) and serum glucose (r=-0.398, p<0.001), whereas, adiponectin correlated significantly with prednisone doses (r=0.241, p=0.015). Patients with higher m-SLEDAI score (≥8) had higher levels of adiponectin (20.88±8.71 vs 15.09±7.51, p=0.032). Conclusions: MIF serum levels were associated to disease activity in SLE, whereas resistin levels correlated with some parameters of renal involvement as well as prednisone doses. We concluded that MIF and resistin should be considered as biomarkers associated to the inflammatory process in some organs in SLE. Founding: This project was supported by Instituto Mexicano del Seguro Social: FIS/IMSS/PROT/G12/1135. References: Hoi AY, Morand EF, Leech M. Is macrophage migration inhibitory factor a therapeutic target in systemic lupus erythematosus? Immunol Cell Biol. 2003;81:367-73. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5670